Frequency constrained predictive control for large scaled spatially distributed systems. (July 2020) - He, Ning; Shen, Chao
Abstract: In this work, a frequency constrained predictive control method is proposed for large scaled spatially distributed systems. A spatial–temporal frequency analysis is first performed to explicitly address the preference of the actuator profile in spatial frequency domain. To achieve the desired actuator profile, the piecewise- and pointwise-spatial frequency (magnitude) constraints are developed, based on which a novel model predictive controller that is able to guarantee the pre-specified requirements on the actuator frequency response is formulated. It is further shown that the proposed frequency constrained model predictive control method can be solved by standard optimization methods. Lastly, a process from the sheet and film industry has been employed to test the effectiveness of the developed method. Highlights: The undesired frequency region of the actuator profile for the cross-directional process is addressed. The piece- and point-wise spatial frequency constraints are developed in quadratic forms. A frequency constrained predictive controller is proposed for the cross-directional process. The effectiveness of the proposed method is illustrated based on an industrial example.